Comprehensive analysis of a hybrid FO/crystallization/RO process for improving its economic feasibility to seawater desalination. (15th March 2020) - Park, Kiho; Kim, Do Yeon; Jang, Yoon Hyuk; Kim, Min-gyu; Yang, Dae Ryook; Hong, Seungkwan
Abstract: In this study, the FO/crystallization/RO hybrid process was analyzed comprehensively, including experimentation, modeling, and energy and cost estimation, to examine and improve its feasibility to seawater desalination. A new operating strategy by heating the FO process to 45 °C was suggested, and a detailed process design was conducted. A comparative analysis with the conventional seawater reverse osmosis (SWRO) process was performed in terms of specific energy consumption (SEC) and specific water cost (SWC). The hybrid process can produce fresh water with SWC of 0.6964 /m 3, electrical SEC of 2.71 kWh/m 3, and thermal SEC of 14.684 kWh/m 3 . Compared to the conventional SWRO process (SWC of 0.6890 /m 3 and electrical SEC of 2.674 kWh/m 3 ), the hybrid process can produce water with comparable cost and energy consumption. An economic feasibility study that utilized the waste heat and the developed FO technology was also carried out to investigate future developments of the hybrid process. The SWC can be reduced to 0.6435 /m 3 with free waste heat energy. The permeate water quality of the hybrid process was about half that of the conventional SWRO process on molar basis. The results revealed that the FO/crystallization/RO hybrid process can be utilized as a competitive process for seawater desalination with high recovery and high water quality. Graphical abstract: Image 1 Highlights: New operation mode of FO/crystallization/RO hybrid process suggested. Applicability of FO/crystallization/RO hybrid process experimentally confirmed. This hybrid process confirmed as cost-competitive for seawater desalination. Utilizing waste heat, water produced at 7% lower cost than that with SWRO. Permeate water quality approximately half of the conventional SWRO on molar basis.